HAK DiNiN TEK OLUŞU - Kayhan, Veli (Fırat University, 2006)
Belief and worshipping are needs which were placed in the nature of mankind. Science and intelligence support this fact. Therefore hurnanbeing is a religios being in nature. In fact "the fitrat" (origination) means "sympatizing divine religion". The religion was set by Allah and it belongs to Him. Allah is the one and only, so the religion must be single. From Adam to Moharnmad (peace be upon them) there is only one divine religion; not divine religions. The religion which all of the prophets brought is the same in origin. There is not any difference between them on the level of belief principles. Other things that systematized and called as a religion aren't celestial; this is a metaphorical calling. This divine teligion was named by Allah: Islam! Then, when the word "religion" was mentioned under all conditions that means "Islam". Its followers were named by Allah as "muslims". All prophets accepted this for the ir peoples. Islam looks at the other religions as a reality. But it doesn't regard them divine. It places them in some special forms in its own system. That is another subject then we dea! with.
Keywords: Religious Studies; Din Araştırmaları